Morfologia dos tricomas em Tibouchina sect. Pleroma (D. Don) cogn. (melastomataceae) - Guimarães, Paulo José Fernandes [UNESP]; Ranga, Neusa Taroda [UNESP]; Martins, Angela Borges (Brazilian Archives of Biology and Technology, 1999)
Melastomataceae é a família que apresenta a maior diversidade de tricomas. Dr. Wurdack em seu Atlas of hairs reconheceu 46 tipos de tricomas para as Melastomataceae neotropicais com o uso de MEV, e referiu 17 destes para o gênero Tibouchina. em Melastomataceae a morfologia dos tricomas tem sido extensivamente usada na delimitação dos táxons, assim como em estudos que antecederam ao trabalho de Cogniaux, a monografia das Melastomataceae brasileiras publicada em 1885. em Tibouchina sect. Pleroma a morfologia dos tricomas foi substancial para a circunscrição de várias espécies. O uso da MEV permitiu uma caracterização dos 15 tipos diferentes de tricomas observados nas 41 espécies examinadas. Os diferentes tipos são descritos com base no aspecto morfológico tanto em MO como em MEV e ilustrados através de eletromicrografias de varredura e fotomicrografias.

The Melastomataceae display greater trichome diversity. Dr. Wurdack, in his Atlas of hairs, recognized 46 types of trichomes for the Neotropical Melastomataceae through the Scanning Electron Microscope (SEM), and referred 17 of them to the genus Tibouchina. The trichome morphology has been extensively used in the delimitation of the taxa in Melastomataceae, as well as in previous studies by Cogniaux, the monograph of Brazilian Melastomataceae published in 1885. The morphology of the trichomes was essential for the delimitation of several species in Tibouchina section Pleroma. The use of SEM provided the best characterization of the 15 different types of trichomes recognized among the 41 species examined. These were described based on the morphological appearance, both optical microscopy and scanning electron microscopy, and illustrated by scanning electron micrographs and photomicrographs.
Keywords: trichome; Morphology; Melastomataceae; Tibouchina